The Origin of the "A In a Circle" As A Symbol of Anarchism: A Symbolic Review of its Development - García-Yeste, Carme; Puente , Ginés (Journal of Cultural Analysis and Social Change, 2026)
The aim of this article is to explore from a historical perspective the origin and evolution of the "A in a circle" symbol, widely associated with anarchism since its creation in Paris in 1964. Documentary and semiotic analysis, which examines how this emblem has become a universal symbol of anarchism, adopted by different movements around the world. In addition, an interview is conducted with the main creator of the symbol. The study, in addition to showing the origin of the symbol, contributes to demystifying certain erroneous beliefs about its origin, and delves into its political and cultural significance in the context of the anarchist struggles of the sixties, seventies and eighties. The conclusions of the article bring us closer to what role the "A in a circle" symbol has acquired in the process of building a globally recognised visual identity for the libertarian movement.